Pengaruh Insentif, Work-Life Balance, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT PLN ULP Pandaan - Anggraeni, Feby Putri; Basalamah, Muhammad Ridwan; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this study is to determine the influence of incentives, work-life balance, work discipline and work motivation on the performance of PT PLN ULP Pandaan employees.  The location of this research is PT PLN ULP Pandaan.  This type of quantitative research uses the case study method with data obtained through distributing questionnaires to all employees of PT PLN ULP Pandaan.  Using the total method with a sample size of 60 respondents. Data were analyzed using multiple linear regression and determination test. Based on these result, the t test shows that the incentives, work-life balance, work discipline and work motivation partially have a significant positive effect on the performance of PT PLN ULP Pandaan employees.  The results of the determination test show a percentage of 93.2% where employee performance can be influenced by incentives, work-life balance, work discipline and work motivation Keywords: Incentives, Work-life Balance, Work Discipline, Work motivation and Employee Performance